PECULIARITIES OF RENDERING PAROEMIOLOGICAL UNITS IN THE UKRAINIAN TRANSLATIONS OF THE WORKS BY MARK TWAIN - Stakhmych , Yu. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the investigation of the peculiarities of rendering paroemiological units in the Ukrainian translations of the works by Mark Twain. The characteristics of paroemiological units have been described. Different types of the units under investigation have been characterized. The types of paroemiological units used in the works by Mark Twain have been defined. The translation methods of paroemiological units have been analyzed. The peculiarities of translating Ebglish paroemiological units in the Ukrainian translation of the shorts stories and novel by Mark Twain have been studied.